PENERAPAN METODE ACTIVITY-BASED COSTING DALAM PENETAPAN TARIF JASA RAWAT INAP PADA RUMAH SAKIT CUT MEUTIA LANGSA - Waleny, Fina Maghfira (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
Â The study aims to determine the application of activity-based costing method in determining the rates of hospitalization services in public hospitals Cut Meutia Langsa. The method used are descriptive and comparative analysis. Data used in the research are primary and secondary data, which are gotten from intern company in 2015. Primary data gotten from interview and direct observation, meanwhile secondary data gotten from hospitalâs cost report.Â The use of the Activity-Based Costing method in the determination of tarrifs for inpatient services presented more accurate and precise. So that the result from this research show that rate of the hospitalization was distored (undercostind and overcosting). Undercosting occur in Super VIP room rates, while the rates for rooms VIP Exclusive, I, II, and III were experienced undercosting.Â Keywordsâ Activity-Based Costing, cost, cost driver, and Â tariff for inpatient serviceÂ